PREVALENSI DAN FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DOUBLE BURDEN OF MALNUTRITION DAN TRIPLE BURDEN OF MALNUTRITION ANAK USIA 5-12 TAHUN DI INDONESIA - Arini Aulia Nurul Fikri (2022)
Double Burden of Malnutrition (DBM) is the coexistence of undernutrition along with overnutrition, meanwhile Triple Burden of Malnutrition (TBM) is a DBM condition accompanied by micronutrient deficiencies. The aim of this study is to determine the prevalence and factors associated with DBM and TBM in children aged 5-12 years in Indonesia. This study used cross-sectional design with secondary data from Riskesdas 2018. Bivariate analysis was carried out with chi-square and multivariate analysis with logistic regression. The results showed that the prevalence of DBM is 3,4% while the prevalence of TBM is 1,4%. This study found a relationship between age (p = 0,033), sex (p = 0,035), place of residence (p = 0,036), diarrhea (p = 0,033) and the incidence of DBM in bivariate analysis. In multivariate analysis, it was found that age 9-12 years (p = 0.042; AOR = 1.512), male sex (p = 0.036; AOR = 1.535) and diarrhea (p = 0.047; AOR = 0.241) were significantly related to the DBM. This study concludes that overall, the prevalence of DBM and TBM in the individual level of children aged 5-12 years is low. Boys and children aged 9-12 years are more at risk of developing DBM.